Pengaruh Perputaran Kas Dan Perputaran Piutang Terhadap Profitabilitas Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia 2020-2022 - Devi Sulistyowati1; G. Anggana Lisiantara (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of The purpose of this study is to evaluate and examine the influence of monetary turnover and income rotation on the yield on the assets (ROA) in food and beverage businesses listed on the stock exchange in Indonesia. (IDX). The subjects in the present research were factories in the Industrial Sector, Food and Beverage Division, enrolled on the Indonesian Securities Exchange. (2020-2022), totaling 18 companies. Based on H1, the financial turnover component from 2020 to 2022 has a significant and beneficial effecti oni Returni Oni Assetsi (ROA) ini foodi andi beveragei companiesi listedi oni thei IDX. Based on H2, the inventory turnover variable hasi ai significanti and beneficial effect on ROA in food and beverage companies listed on the IDX in 2020 and 2022. Based on H3, cashi turnoveri andi accountsi receivablei turnoveri havei ai goodi andi significanti effecti oni ROA ini foodi and beveragei companiesi listedi oni the IDX in 2020-2022.